Penerapan Manajemen Pembelajaran Untuk Meningkatkan Mutu Pendidikan Di SD Cendana Batam - Afridoni Afridoni; Muhammad Syaifuddin; Syairaini Tambak (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
The quality of education in Indonesia is still not improving, although various efforts have been made to improve it, this is because the teacher's responsibility is not only limited to the process of transferring knowledge but one thing that teachers need to pay attention to is their expertise in managing learning, therefore it is necessary implementation of learning management is done well. A professional teacher not only transfers knowledge but also must be able to manage all existing educational resources, especially in the learning process the teacher must be able to manage the learning that will be delivered starting from planning, organizing, implementing and monitoring/evaluating. The author's suggestion for a teacher must also understand the concept of good learning management, the principles of good management, the characteristics of good learning management, and the goals of learning management itself so that it can achieve the goals of education.